2017
DOI: 10.1016/j.adro.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prone versus supine positioning on small bowel dose with pelvic intensity modulated radiation therapy

Abstract: PurposeTo report the results of a prospective study that compares small bowel doses during prone and supine pelvic intensity modulated radiation therapy.Methods and materialsTen patients receiving pelvic radiation therapy each had 2 intensity modulated radiation therapy plans generated: supine and prone on a belly board (PBB). Computed tomography on rails was performed weekly throughout treatment in both positions (10 scans per patient). After image fusion, doses to small bowel (SB) loops and clinical target v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Several studies have demonstrated that prone positioning provides enhanced normal tissue sparing in certain clinical scenarios. [6][7][8] Mullinez et al 6 conducted a study in 18 early-stage breast cancer patients who were undergoing whole-breast irradiation after having breast-conserving surgery. Dosimetric evaluation of plans for 6 patients comparing tangential wedge fields, tangential field IMRT, and multi-beam IMRT was performed in supine and prone for each patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that prone positioning provides enhanced normal tissue sparing in certain clinical scenarios. [6][7][8] Mullinez et al 6 conducted a study in 18 early-stage breast cancer patients who were undergoing whole-breast irradiation after having breast-conserving surgery. Dosimetric evaluation of plans for 6 patients comparing tangential wedge fields, tangential field IMRT, and multi-beam IMRT was performed in supine and prone for each patient.…”
Section: Discussionmentioning
confidence: 99%
“…The prone positioning did, however, significantly reduce the small bowel dose V5 and V10 volumes. 5 Ten patients undergoing pelvic radiation therapy were evaluated with both prone and supine treatment plans by Gonzales et al 8 to compare small bowel dose. They found that prone positioning resulted in a lower volume of small bowel receiving irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation exposure of intestines is better in prone position with the use of BB, than in supine position, in case of 3D-CRT and IMRT technique, which may decrease the GI morbidity in itself (9). Gonzalez et al (10) found that a significantly smaller volume of the small intestine receives more than 20 Gy dose in prone position with the use of BB, while the interfraction dose variation to the small bowel was similar to the supine position. Bajon et al (11) have shown decreased dose exposure of the urinary bladder in prone position besides sparing the rectum and the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation fields become widely used like radiological, diagnostic imaging, radiation therapy, nuclear and industrial applications thus fields can be harmful to human due to hazards radiation. The choice of shielding material has gained more attention to reduce biological effects of radition and depend on type of radiation, energy of that radiation and characteristics of the chosen material [34].…”
Section: Characteristics Of Calcinated Bentonite Claymentioning
confidence: 99%